State environmental security in national and globalization aspects - Bezpalova, O. I.; Безпалова, О. І.; Onopriienko, S.; Tarasov, S.; Zavalna, Z.; Starynskyi, M. (Journal of Security and Sustainability Issues. – 2020. – № 9 (3). – Р. 797-806., 2020)
Стаття присвячена вивченню екологічної безпеки держави у національному та глобалізаційному аспектах. Встановлено, що екологічна безпека держави – це збереження та захист життєдіяльності, інтересів людини та навколишнього середовища від негативних антропогенних та природних факторів, що є важливою складовою безпеки держави. Встановлено, що з поняттям «екологічна безпека» існує поняття «екологічна модернізація» як подолання негативних впливів на довкілля із боку індустріального суспільства шляхом перетворення останнього з допомогою новітніх технологій. Визначено існуючі загрози екологічній безпеці України, що зазначені у Стратегії національної безпеки України 2015 року. Пропонується не лише доповнити завдання Міністерства екології та природних ресурсів щодо розробки єдиного переліку показників рівня ЄС для оцінки стану навколишнього середовища, а й залучити громадськість до повноцінної участі в управлінні природокористуванням.

The article is devoted to the study of the state environmental security in national and globalization aspects. It has been established that the environmental security of the state is a status of every person's security, society, state and nature from excessive danger to the environment, i.e. the preservation and protection of vital activity, individual's interests and his environment from negative anthropogenic and natural consequences, which is an important component of the state security. It is established that together with the concept of "environmental security" there is a concept of "environmental modernization" as overcoming of negative impacts on environment from the industrial society by transformation of the latter with help of the latest technologies. The existing threats to Ukraine's environmental security, identified in the National Security Strategy of Ukraine in 2015 have been determined. The need for additional attention to the armed conflict in eastern Ukraine was emphasized as one of the threats to the states's economic security, which is in line with the provisions of the United Nations Resolution "Environmental Protection in Areas Affected by Armed Conflict". It is noted that the Ministry of Ecology and Natural Resources only formally fulfills the task of assessing the environmental status, unlike Finland and Sweden. The issue of public participation of Ukraine in environmental management is still debatable, as defined by the Law of Ukraine "On Environmental Protection", it remains only formal, although, for example, the public is actively involved in the management of this field in China. Accordingly, it was proposed not only compliting tasks by the Ministry of Ecology and Natural Resources to develop a single list of indicators at EU level for assessing the environment status, but also to involve the public in full participation in environmental management. © 2020 General Jonas Zemaitis Military Academy of Lithuania.

Статья посвящена изучению экологической безопасности государства в национальном и глобализационном аспектах. Установлено, что экологическая безопасность государства – это сохранение и защита жизнедеятельности, интересов человека и окружающей его среды от негативных антропогенных и природных факторов, что является важной составляющей безопасности государства. Установлено, что наряду с понятием «экологическая безопасность» существует понятие «экологическая модернизация» как преодоление негативных воздействий на окружающую среду со стороны индустриального общества путем преобразования последнего с помощью новейших технологий. Определены существующие угрозы экологической безопасности Украины, обозначенные в Стратегии национальной безопасности Украины 2015 года. Предлагается не только дополнить задачи Министерства экологии и природных ресурсов по разработке единого перечня показателей уровня ЕС для оценки состояния окружающей среды, но и привлечь общественность к полноценному участию в управлении природопользованием.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Земельне право. Екологічне право. Аграрне право. Land Law. Environmental law. Agrarian Law. Земельное право. Экологическое право. Аграрное право; екологія; довкілля; моніторинг довкілля; екологічна безпека; ecology; environmental monitoring; environmental security; security; suburban environment экология; окружающаяя среда; мониторинг окружающей среды; экологическая безопасность